Simplify

[tex] \sqrt[6]{x} ^{16} [/tex]

A. [tex] x^{8} [/tex]

B. X*[tex] \sqrt[6]{x} ^{16} [/tex]

C. [tex] x^{2} [/tex]*[tex] \sqrt[6]{x} ^{4} [/tex]

D. [tex] x^{6} [/tex]*[tex] \sqrt[5]{x} ^{4} [/tex]

Respuesta :

if you mean [tex]\sqrt[6]{x^{16}} [/tex] and not [tex](\sqrt[6]{x})^{16} [/tex]  then

remember[tex] \sqrt[n]{x^m} =x^ \frac{m}{n} [/tex]
and
[tex]x^{m+n}=(x^m)(x^n)[/tex]
so
[tex]\sqrt[6]{x^{16}}= x^\frac{16}{6}=(x^\frac{12}{6})(x^\frac{4}{6})[/tex]=
[tex](x^2)(x^\frac{4}{6})=x^2 \sqrt[6]{x^4} [/tex]

C is answer